The Role of Fear of Failure and Self-Efficacy in Student Engagement among Indonesian University Students: A Predictive-Correlational Study - Lailatuzzahro A. Aulia; Estalita Kelly; Arinal Chusnah; Aizun Riski Safitri; Indasah Indasah (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2026)
This study examined the effects of fear of failure and self-efficacy on student engagement among undergraduate students at a private university in East Java, Indonesia. A quantitative predictive-correlational design was employed with 215 undergraduates (155 female, 60 male; age M = 20.4, SD = 1.38) recruited through purposive sampling. Data were collected using three self-report scales: the Student Engagement Scale (28 items; α = .887) based on Fredricks et al. (2004), the Fear of Failure Scale (26 items; α = .891) based on Conroy (2001), and the General Self-Efficacy Scale (Schwarzer & Jerusalem, 1995; 10 items; α = .908). Multiple linear regression analysis revealed that fear of failure had a significant negative effect on student engagement (β = −.757, p < .001) and emerged as the dominant predictor. In contrast, self-efficacy exerted a smaller but statistically significant positive effect (β = .100, p = .023). Together, both predictors accounted for 60.1% of the variance in student engagement (Adjusted R² = .601; F(2, 212) = 163.359, p < .001). Fear of failure was thus the dominant predictor, with a substantially larger standardized coefficient and a considerably greater share of unique variance than self-efficacy. Because the design was cross-sectional and all constructs were measured through self-report at a single time point, these findings should be interpreted as associations rather than causal effects. The results tentatively suggest that, in this context, reducing evaluative threat may warrant as much attention as strengthening confidence when designing academic environments that foster student engagement